The rock art of San Juan de Yarucaya, district of Cochamarca, Oyón - van Dalen Luna, Pieter D. (2021)
The Sierra of Lima presents a great variety of archaeological sites with quilcas or cave paintings, which correspond to different pre-Hispanic chronological periods. In the present study we present the registry of three sites with paintings located in the Campesino Community of Yarucaya, Oyón district; constituting one of the first references on rock art in this province, so close to Lima, but so forgotten by archeology.